HARMONICS PSEUDO-MEASUREMENT ESTIMATION AND PREDICTION - ARUMUGAM, UGASCINY (2013)
In power distribution system across the world, the need to maintain its power quality remains crucial. As technology takes over various aspects of life, the amount of non-linear equipment has been increasing, forming distortion in the distribution network. Thisis mainly dueto the harmonics current injected by non-linearloads into the distribution line,whichthen pollutesthe power qualityand posesrisks and losses. Various measures have been identified to overcome these unwanted harmonics in the distribution line.